Carbon dots derived fluorescent nanosensors as versatile tools for food quality and safety assessment: A review. (January 2020) - Luo, Xueli; Han, Yong; Chen, Xiumei; Tang, Wenzhi; Yue, Tianli; Li, Zhonghong
Abstract: Background: Food analysis is essential in monitoring food quality for risk assessment regarding public health. Traditional techniques can meet the requirement of routine food analysis in laboratory. However, serious food safety situations urgently demand rapid, time-saving, low-cost analysis methods even on-site, portable and household testing kits. Fluorescence analysis exhibits immense potential for food safety owing to its remarkable advantages of high sensitivity, ease of operation, low cost and rapid result outputs. Scope and approach: Carbon dots (CDs) are novel 0D carbonic nanomaterials recently emerging as potential substitutes for traditional fluorescent materials. Compared with the conventional fluorescent materials, e.g. organic fluorescent dyes, metal nanoparticles/nanoclusters and quantum dots (QDs), CDs possess many appealing merits such as ease of preparation, low cost, non-blinking, low cytotoxicity, excellent biocompatibility and high resistance to photo-bleaching. As a result CDs-based fluorescence sensing provides excellent analysis platforms for monitoring food-related analytes. This review provides a comprehensive overview of the state-of-the-art synthesis methods and the fluorescence properties of CDs along with the sensing mechanisms and designing principles of CDs-based fluorescent sensors for food analysis. Possible challenges and appealing prospects of CDs-based fluorescent sensors are also discussed. Key findings and conclusions: CDs have been widely applied in bio-imaging, sensing, drug delivery, catalysis and optronics. Integration of CDs into food science and engineering for food safety control and risk assessment exhibits a bright future. Graphical abstract: Image 1 Highlights: Fluorescence properties for reducing interferences to food safety screening. Fluorescence response mechanisms of CDs-based fluorescent sensors. Designing and analysis principles of CDs sensors for food analysis. Selectivity improving and interference reducing for practical applications. New trends in material, ligands and portable sensors designing.